Short‐peptide fusion inhibitors with high potency against wild‐type and enfuvirtide‐resistant HIV‐1. Issue 3 (11th December 2012) - Chong, Huihui; Yao, Xue; Qiu, Zonglin; Sun, Jianping; Zhang, Meng; Waltersperger, Sandro; Wang, Meitian; Liu, Shan‐Lu; Cui, Sheng; He, Yuxian
Abstract : Peptides derived from the C‐terminal heptad repeat (C peptides) of HIV‐1 gp41 are potent inhibitors against virus entry. However, development of a short C peptide possessing high anti‐HIV potency is considered a daunting challenge. We recently discovered that the residues Met626 and Thr627 preceding the pocket‐binding domain of the C peptide adopt a unique M‐T hook structure that is crucial for the design of HIV‐1 fusion inhibitors. In this study, we first presented a proof‐of‐concept prototype that the M‐T hook residues can dramatically improve the antiviral activity and thermostability of a short C peptide. We then generated a 24‐mer peptide termed MT‐SC22EK by incorporating the M‐T hook structure to the N terminus of the poorly active short C peptide SC22EK. Amazingly, MT‐SC22EK inhibited HIV‐1‐mediated cell fusion and infection at a level comparable to C34, T1249, SC29EK, and sifuvirtide, and it was highly active against diverse HIV‐1 subtypes and variants, including those T20 (enfuvirtide) and SC29EK‐resistant viruses. The high‐resolution crystal structure of MT‐SC22EK reveals the N‐terminal M‐T hook conformation folded by incorporated Met626 and Thr627 and identifies the C‐terminal boundary critical for the anti‐HIV activity. Collectively, our studies provide new insights into the mechanisms of HIV‐1 fusion and its inhibition.—Chong, H., Yao, X., Qiu, Z., Sun, J., Zhang, M., Waltersperger, S., Wang, M., Liu, S.‐L., Cui, S., and He, Y. Short‐peptide fusion inhibitors with high potency against wild‐type and enfuvirtide‐resistant HIV‐1. FASEB J. 27, 1203–1213 (2013). www.fasebj.org